Reservoir sedimentation handbook : design and management of dams, reservoirs, and watersheds for sustainable use - Morris, Gregory L.; Jiahua, Fan. (New York : McGraw-Hill, 1998)
This book contains: Reservoirs and Sustainable Development; Engineering Features of Dams and Reservoirs...
Keywords: Reservoir sedimentation; Reservoir sedimentation